Avaliação automatizada de estética de jogos genéricos de cartas e dados - Vanderley, Augusto Acioli Pinho (2018)
Understanding the feeling that playing a game provides to the player is quintessential to game design. As playtesting is difficult and expensive, Automatic Game Design has been an area that keeps growing and getting much attention. The present work aims to offer a tool for automatic avaliation of dice and card games. Therefore, this work presents RECYCLEDICE, a language that allows card and dice games to be descripted. Furthermore, a tool was adapted to interpret and simulate games, playing automatically and generating statistics from gameplaying. Lastly, simulations and aesthetics metrics, such as drama, lead change and uncertainty, were combined in order to generate relevant information about the game.